2015
DOI: 10.14407/jrp.2015.40.3.187
|View full text |Cite
|
Sign up to set email alerts
|

Changing of RGS Transcripts Levels by Low-Dose-Rate Ionizing Radiation in Mouse Testis

Abstract: Deleterious effects of high dose radiation exposure with high-dose-rate are unarguable, but they are still controversial in low-dose-rate. The regulator of G-protein signaling (RGS) is a negative regulator of G proteincoupled receptor (GPCR) signaling. In addition, it is reported that irradiation stress led to GPCR-mediated mitogen-activated protein kinase (MAPK) and phosphotidylinositol 3-kinase (PI3-k) signaling. The RGS mRNA expression profiles by whole body radiation with low-dose-rate has not yet been exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, in another study, it was reported that membrane-bound receptors for hormones, cytokines, growth factors or neurotransmitters are implicated in various sperm functions, such as motility and capacitation [ 72 ]. Moreover, RGS18 belongs to the G-protein signaling family, which inhibits signal transduction by increasing the GTPase activity of G protein alpha subunits [ 73 ] and it is expressed in the testis [ 74 ]. Our findings suggest that the co-expression of cis -regulating DElncRNA with GHR , THRB or RGS18 was associated with increased sperm cryo-damage, however, the functions of these genes in sperm freezability are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, in another study, it was reported that membrane-bound receptors for hormones, cytokines, growth factors or neurotransmitters are implicated in various sperm functions, such as motility and capacitation [ 72 ]. Moreover, RGS18 belongs to the G-protein signaling family, which inhibits signal transduction by increasing the GTPase activity of G protein alpha subunits [ 73 ] and it is expressed in the testis [ 74 ]. Our findings suggest that the co-expression of cis -regulating DElncRNA with GHR , THRB or RGS18 was associated with increased sperm cryo-damage, however, the functions of these genes in sperm freezability are unclear.…”
Section: Discussionmentioning
confidence: 99%